THE EFFECTS OF SOAKING EXTRACTS OF STEMS Musa Acuminate AND LEAVES Ocimum Basilicum L. ON FLUORIDE RELEASE OF WATER SETTABLE GIC - Gusti Wina Ayu Hazarisa; Sherli Diana; Nurdiana Dewi (Dentin, 2023)
Background: Mouthwash is a dental and oral health product that is easy to obtain and practical to use. Mouthwash is able to kill bacteria causing dental and oral health problems. Mauli banana stems and Basil leaves can be used as an alternative to natural mouthwash because they contain bioactive compounds such as saponins, alkaloids, lycopene, ascorbic acid, flavonoids, and tannins. Objective: To analyze the effect of a mixture of extracts of Mauli banana (Musa acuminate var. sapientum) stems and Basil leaves (Ocimum basilicum L.) at concentrations of 75% and 100% on fluoride ion release in the Water Settable GIC. Methods: Pure experimental design with post-test only with control group design. The number of samples consisted of 21 samples, which were divided into 3 treatment groups, and then the value of fluoride ion release was measured after 22 hours. Results: One Way Anova test showed a significant difference with p <0.05 among the treatment groups. The results of the Post Hoc Bonferroni test obtained a p-value of <0.05, which means that there was a significant difference between the control group compared to the extracts of Mauli banana stems and Basil leaves at concentrations of 75% and 100%. Conclusion: There was an effect of the mixture of the extracts of Mauli banana (Musa acuminate var. sapientum) stems and Basil leaves (Ocimum basilicum L.) at concentrations of 75%, 100%, and artificial saliva on fluoride ion release in the Water Settable GIC. Keywords: Basil Leaves, Fluoride Ion, Mauli Banana Stems, Water Settable.